Dementia becoming popular. Representations of a cultural phenomenon in contemporary fiction, the arts, and mainstream media (KULT_online, 2016)
Editors Aagje Swinnen and Mark Schweda assemble a variety of expertise from different disciplines, and a range of methods and research designs to critically investigate the representation and the popularization of dementia in literary fiction, the visual arts, and the mass media. The volume sheds light on the communication processes at work and the images of dementia ranging from negative stereotypes to new and alternative discourses. It hints at the crucial and delicate role of mainstream media in the information society – especially when it comes to a phenomenon such as dementia – threatening the agency of those affected. With a very broad scope, this book continues to raise awareness and provides stimuli for research as well as activism.